Analisis Komparatif Hukum Pidana Indonesia Dan Fiqh Jinayah Terhadap Kekerasan Dalam Rumah Tangga Yang Dilakukan Istri Terhadap Suami - Nurmala, Ayu; Iwan, Iwan (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2025)
Domestic violence (DV) refers to acts of violence committed by family members against other family members, which can be physical, sexual, psychological or spiritual. In some cases, the perpetrator of domestic violence is not only the husband, but also the wife. This study aims to analyze the form of domestic violence, the perspective of Islamic criminal law on domestic violence, and the settlement of domestic violence cases committed by wives against husbands according to the Marabahan District Court Decision Number 80/Pid.Sus/2016/PN.Mrh. This research uses normative research methods. The results showed that domestic violence is regulated in Law No. 23 of 2004 and Article 351 of the Criminal Code. In Islamic criminal law, the disobedient wife (nusyuz) is classified as jarimah qisas-diyat. In the verdict, the perpetrator was punished with ta'zir, although the punishment was considered too light to provide a sense of justice for the victim.